Recurrence of cardiac myxoma. Clinical and morphological aspects - I. M. Iljinsky; A. S. Ivanov; M. K. Lugovsky; N. P. Mozhejko (Вестник трансплантологии и искусственных органов)
Aim: to conduct a one-center retrospective research of heart myxoma relapses in a large group of patients. Materials and methods. Since 1992 to 2016 115 surgical removal of sporadic cardiac myxoma was performed (44 male, 71 female).Results. Two (1.7%) patients had recurrence of sporadic myxoma of the left atrium. One patient had the tumor returned due to inadequate removal of the tumor. Myxoma was removed without excising the place of ﬁ xation to the interatrial septum. The second patient possibly had recurrence of myxoma due to the conservation of a small tumor fragment in another part of the interatrial septum that was not diagnosed during the removal of the primary tumor. Conclusion. Recurrence of sporadic myxoma of the left atrium is rare. The reasons for the recurrence may be different but usually it is due to non-radical removal of the tumor. The results of our research show that even removal of the myxoma together with the interatrial septum does not fully guarantee the prevention of recurrence. The recurrence of sporadic cardiac myxoma is possibly associated with minor formations that are not diagnosed during surgery. We cannot exclude the possibility of forming myxoma denovo also.